Identification of SARS-CoV-2 variants of concern in vaccine-breakthrough infections - Baha Abdalhamid; Matthew Donahue; Ishrat Kamal-Ahmed; Kyle Strand; Elizabeth Mitchell; Peter C Iwen (Journal of Infection in Developing Countries)
Not Applicable